Evaluation of Thermal, Acoustic, and Physical Properties of Bamboo Ceiling Panels Made from Three Species - Muhammad Amirul Adli Safuan; Saji, Nurdalila; Mohammad Ashraf Abdul Rahman; Najeeha Mohd Apandi; Puteri Sophia Shamsuri (Journal of Advanced Industrial Technology and Application, 2025)
Bamboo has gained attention as a sustainable alternative to conventional ceiling materials, which often suffer from issues such as poor moisture resistance and limited durability. This study evaluates the thermal, acoustic, and physical properties of ceiling panels produced from three bamboo species which are Gigantochloa scortechinii, Dendrocalamus asper, and Gigantochloa levis, bonded with phenol formaldehyde. The panels were fabricated in strip form and tested for density, thermal conductivity, water absorption, and sound absorption using standard laboratory methods. Results show that Dendrocalamus asper exhibited the best overall performance, achieving the lowest thermal conductivity (0.043 W/m·°C) and the highest sound absorption coefficient at high frequencies (1.311 at 4000 Hz). These findings demonstrate that bamboo-based ceiling panels, particularly those made from Dendrocalamus asper, offer strong potential as energy-efficient and acoustically effective alternatives to gypsum ceilings.